Responses of Photosystem I Compared with Photosystem II to Fluctuating Light in the Shade-Establishing Tropical Tree Species Psychotria henryi - Huang, Wei; Yang, Ying-Jie; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2016)
Shade-establishing plants growing in the forest understory are exposed to constant high light or fluctuating light when gaps are created by fallen trees. Our previous studies indicate that photosystem I (PSI) is sensitive to constant high light in shade-establishing tree species, however, the effects of fluctuating light on PSI and photosystem II (PSII) in shade-establishing species are little known. In the present study, we examined the responses of PSI and PSII to fluctuating light in comparison to constant high light in the shade-establishing species Psychotria henryi. Accompanying with significant activation of cyclic electron flow (CEF), the P700 oxidation ratio was maintained at high levels when exposed to strong light either under fluctuating light or constant high light. Under moderate fluctuating light, PSI and PSII activities were remained stable in P. henryi. Interestingly, PSI was insusceptible to fluctuating light but sensitive to constant high light in P. henryi. Furthermore, both PSI and PSII were more sensitive to constant high light than fluctuating light. These results suggest that CEF is essential for photoprotection of PSI under fluctuating light in P. henryi. Furthermore, photoinhibition of PSI under high light in P. henryi is more related to the accumulation of reactive oxygen species rather than to P700 redox state, which is different from the mechanisms of PSI photoinhibition in Arabidopsis thaliana and rice. Taking together, PSI is a key determiner of photosynthetic responses to fluctuating light and constant high light in the shade-establishing species P. henryi.